062 Basic Research to Determine Normal Levels of Androgens (Testosterone, Free Testosterone, DHEA-S) in Japanese Middle-Aged Women. (1st May 2022) - Sekiguchi, Y.; Kumamoto, Y.; Nakamura, R.; Minami, K.; Fujii, M.
ABSTRACT: Introduction: We surveyed the age distribution (30-80s) of blood androgen levels (testosterone, free testosterone, DHEA-S) in healthy Japanese women at the testing center currently used by general clinicians measure by method for creating androgen reference values ​​of Japanese women. In addition, the major female hormones estradiol, the gonadotropins LH and FSH, and IGF-1, which reflected growth hormone were measured at the same time. Objective & Methods: We collected the bloods of 160 healthy volunteer women who visited the Women's Clinic LUNA JAPAN, Sapporo Toho Hospital, and Caress Sapporo Clock Tower Memorial Hospital between Oct. 2020 and Feb.2021 and measured testosterone, free testosterone, DHEA-S, estradiol, LH, FSH and IGF-1. The measurement was outsourced to the Biochemical Blood Testing Department of LSI Medience Corporation, and the androgen level was collectively measured by the CLIA method. The survey was conducted with the approval of the medical corporation LEADING GIERLS Ethics Committee and with the written consent of all patients. Results: The average age of volunteer women was 45, the median was 41, the maximum was 87, and the minimum was 20. The number distribution was 16 in their 20's, 52 in their 30's, 43 in their 40's, 17 in their 50's, 15 in their 60's, 10 in their 70's, and 7 in their 80's. Table 1 shows the mean ± standard deviation of testosterone, free testosterone, DHEA-S, LH, FSH, estradiol, and IGF-1 for each age group. (Table 1) Conclusions: In this group, regarding male hormones, DHEA and free testosterone decreased with age. In addition, IGF-1 also decreased with age. On the other hand, with regard to testosterone, the level of decrease is smaller than those of the other two androgens. Regarding estradiol, it decreased rapidly after menopause, but it is maintained at 10 to 20 pg / ml even after menopause. Healthy middle-aged women in Japan may maintain the lowest levels of testosterone and estradiol by eating a diet rich in sex hormone-like flavonoids such as soy isoflavones. However, the sexual function of healthy middle-aged and elderly people in Japan is said to be lower in both men and women than in Europe and the United States, and further research is needed on the relationship between Japanese sex hormone levels and sexual function and culture. Disclosure: Work supported by industry: no.